Les caractéristiques du syndicalisme minier français et son apport au mouvement ouvrier français - Trempé, Rolande (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1981)
AbstractIn France, until 1914, the trade unionism of miners developed in an original way. It was a movement of industrial unionism characterized by a marked spirit of corporatism, which was soon organized on the national and international levels through federations of miners. The miners' movement had difficulties fitting in with other union organizations. The Confédération Nationale du Travail did not include miners until 1908.This late involvement resulted in part from the miners' own methods. Right from the start, they mobilized to obtain protective laws. Union organization and the strike were used as means of pressure in order to force Parlement and the government to take the miners' demands into account. Although such methods were not accepted by the more radical French labour legislation owes much to the battles of the miners. It was they who signed the first collective agreements and who practised systematic bargaining to resolve disputes over wages. By the power of their organization and commitment, the miners led the way to the sweeping trade unionism of today.